The Universal Thermal Climate Index (UTCI) Principles Underpinning and Possibility of its Application in Arid Environments (Iraq Case Study) - دحام مصلح السبهاني, خميس (Al-Adab Journal, 2018)
The objective of this study is to introduce the principles that the UTCI underpinning it, with statistical modeling of the index. Then testing the possibility of evaluates human sensations to climate conditions in arid environment by using UTCI (Iraq case study). To achieve this goal we analysis four climatic parameters from twenty sixth stations in Iraq over the period 1980 – 2013. The results show heat stress levels and bioclimatic conditions in arid environment can be determined using the UTCI scale, due to that the UTCI the most realistic way actual physiological responses of an organism to climate situation. Our finding shows the Iraqi climate tends to extreme heat stress more than sever cold stress, where the highest two categorizes of cold stress disappeared from our maps for all months and, situations and stations. However, the category of extreme heat stress frequently was occurring with maximum temperature during the summer months only. The results also show that the complete optimum thermal comfort for all stations with minimum temperature was occurring in five months (April, May, June, September and October). While optimum thermal comfort was frequent for four months with mean temperature (April, October, November, and December). During day “maximum temperature” the optimum thermal comfort was occurring only in two months (November and December).